1988
DOI: 10.1007/bf01790098
|View full text |Cite
|
Sign up to set email alerts
|

Linkage studies do not confirm the cytogenetic location of incontinentia pigmenti on Xp11

Abstract: Linkage studies have been performed in 5 incontinentia pigmenti (IP) families totaling 29 potentially informative meioses. Ten probes of the Xp arm were used, six of them were precisely localized on the X chromosome, using hamster X human somatic cell hybrids containing a broken X chromosome derived from an incontinentia pigmenti patient carrying an X;9 translocation [46,XX,t(X;9)(p11.21;q34)]. The following order for probes is proposed: pter - (DXS7, DXS146, DXS255) - IP1 - (DXS14, DXS90) - DXS106 - qter. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…30830) was assigned to X pll.2 at previous workshops on the basis of a number of females with X;autosome translocations involving the same apparent X chromosome breakpoint and one case involving a ring chromosome encompassing the same region of the X (deGrouchy et al 1985;Gilgenlcrantz et al 1985;Hodgson et al 1985;see discussion in Davies et al HGM9). This localization is not supported by recent linkage studies of familial IP (Sefiani et al 1988a;Harris et al 1988a).…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…30830) was assigned to X pll.2 at previous workshops on the basis of a number of females with X;autosome translocations involving the same apparent X chromosome breakpoint and one case involving a ring chromosome encompassing the same region of the X (deGrouchy et al 1985;Gilgenlcrantz et al 1985;Hodgson et al 1985;see discussion in Davies et al HGM9). This localization is not supported by recent linkage studies of familial IP (Sefiani et al 1988a;Harris et al 1988a).…”
mentioning
confidence: 62%
“…Molecular heterogeneity in the IP1 breakpoints has been demonstrated by Sefiani et al (1988a) and by Crolla and Bobrow (1988). Sefiani et al demonstrated using somatic cell hybrids that the breakpoint in one X;autosome translocation case of IP is located in Xpll.21, distal to DXS90 and DXS14.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…These anomalies have never been reported in familial cases of IP. Furthermore, linkage studies excluded linkage to the Xpll region in the series of familial cases (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Thus, some authors contest the validity of the diagnosis of IP in sporadic cases that phenotypically resemble IP (12).…”
Section: Discussionmentioning
confidence: 99%
“…To promote medical research in Morocco, serious efforts and several strategic goals must be agreed on by all stakeholders, scientists, and decision makers. The strategy should include upgrading research infrastructure and equipment, providing sufficient funds and (Sefiani et al 1988;Tajir et al 2012;Grant et al 2013;Makrythanasis et al 2014;Mansouri et al 2014;Natiq et al 2014;Qrafli et al 2014Qrafli et al , 2014Janati Idrissi et al 2015;Ratbi et al 2015;Twigg et al 2015;Elalaoui et al 2016;Guaoua et al 2016;Jouali et al 2016 International University (UIASS) and Paris (Imagine) Institute of genetic diseases, the main genetic research institute in France. The objective aims to better understand genetic diseases, bringing diagnostic, and therapeutic solutions to Moroccan patients and their families (Doctinews, 2016) • A laboratory of genetic engineering will be created at Fes Euro-m editerran eenne University.…”
Section: Research In Geneticsmentioning
confidence: 99%